Efforts to Increase Local Community Income Through Seaweed Cultivation in Arareni Village Yapen Islands Regency - Efray Wanimbo; Kalvin Paiki; Lodwyk Nomensen Krimadi (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2023)
Papua has various kinds of potential marine natural resource wealth, both biological and non-biological natural wealth. The potential of these natural resources should be utilized to improve the community's economy. Utilization of the potential of marine resources is still far from expectations. One of the potential marine resources is seaweed. Seaweed has export potential, and its economic value is met from cultivation activities. The aim of this community partnership empowerment (PKM) activity is to increase the knowledge of small-scale seaweed farmers and implement pre-harvest seaweed cultivation practices in Arareni Village, Yapen Islands Regency. The approach used is the delivery of material through socialization related to cultivation practices, starting from the land preparation process, seeding, maintenance, calculating harvest time and yields, as well as group management. During the socialization there were also questions and answers and discussions. The success of the activity is evaluated through a pre-post test. The results show that the highest increase in knowledge was achieved in the cultivation process material (pre-test 47% and post-test 61%). Seaweed farmers know that the seed production age is 25-30 days, harvest after 30-45 days, seed weight 50-100 grams, maintenance takes 25-30 days, distance between ropes 100-200 cm, seeds must be 20-50 cm apart below the water surface and the yield size is 250 g/rope.